2018
DOI: 10.1111/jsbm.12398
|View full text |Cite
|
Sign up to set email alerts
|

Using Mind Maps to Distinguish Cultural Norms between French and United States Entrepreneurship Students

Abstract: The globalization of entrepreneurship education requires instructors to understand, and adjust the curriculum for, cultural disparities. This study investigates the impact of cultural norms on the attitudes of university entrepreneurship students in France and the United States—regions with contrasting Hofstede and Global Entrepreneurship Monitor indices. It uses mind maps from students as culturally agnostic open‐ended measures of their attitudes. Two mind maps were collected from each student, one on the app… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(23 citation statements)
references
References 53 publications
(63 reference statements)
0
15
0
3
Order By: Relevance
“…Second, existing studies on the influence of entrepreneurship education on entrepreneurial intention are based on the development of already developed Western countries. Entrepreneurial educators should adjust curricula in view of cultural differences in learning (Bandera et al, 2018 ). The growing emphasis on entrepreneurship education in Asia, especially China, and the increasing number of students participating in business plan competitions allow students to focus on skills that can be applied to business practices in home countries.…”
Section: Discussionmentioning
confidence: 99%
“…Second, existing studies on the influence of entrepreneurship education on entrepreneurial intention are based on the development of already developed Western countries. Entrepreneurial educators should adjust curricula in view of cultural differences in learning (Bandera et al, 2018 ). The growing emphasis on entrepreneurship education in Asia, especially China, and the increasing number of students participating in business plan competitions allow students to focus on skills that can be applied to business practices in home countries.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, Damanpour [52] found that the cultural innovation of large companies has a significant positive impact on performance. Bandera et al [53] compared the cultural norms of France and the United States and found that corporate culture plays an important role in the growth of companies. In addition, several studies have investigated the impact of innovation culture on firm performance [48,[54][55][56].…”
Section: Innovation Culturementioning
confidence: 99%
“…Finalmente, a terceira vertente mostra que a RSL retornou artigos de ensino-aprendizagem do empreendedorismo alusivo à MPE. Diversos estudos revelam que o mercado de trabalho exige que os educadores entendam e ajustem o currículo às disparidades culturais pertinentes as atitudes, autopercepções, competências, habilidades, valores e intenções dos estudantes universitários em relação ao comportamento organizacional em empresas de pequeno porte (Bandera et al, 2018;Franchetti & Ariss, 2017;Gamede & Uleanya, 2019;Gargouri & Naatus, 2019;Ghina, Simatupang & Gustomo, 2017;Ladeveze & Canal, 2016;Nguyen & Nguyen, 2018;Ramona-Diana, 2017;Saji & Nair, 2018). Outras investigações ainda abordam o empreendedorismo como forma de apoiar o discente de engenharia de produçãoe outros cursosa exercer a profissão em pequenas empresas, como evidenciado nos artigos de Glackin, Byrd e Phelan (2016), Jones e Liu (2017), Marliyah (2018), Michael (2018), Santoso (2017) e Sun et al (2017.…”
Section: Discussionunclassified